A implementação do sistema de informação de custos do setor público: o caso do governo federal - Gnisci, Eduardo Francisco dos Santos (2010)
In the development of Brazilian public administration stand out significant initiatives to improve the quality of public spending. This issue has figured in many discussions in public and academic environment and brings about an opportunity for optimization of public action through the effective control of their costs. Since the 60s the Brazilian public management expects to implement a system capable of presenting the faces of the cost as well as monitoring the activities of management in terms of their cost-benefit. However only after the first decade of the twenty-first century appear concrete actions with the intention of moving toward a standard cost system to be adopted by government and its various agencies and entities. Therefore, this study is to search this implementation process and to describe the interfaces with other management subsystems. This research was based on national and international experiences of implementing cost systems aimed at understanding the foundations that guided the creation and deployment of the Brazilian model. The aim therefore is to seek a grant that aims to clarify the initiative of the Ministry of Finance of the creation of this system, which agrees with the legal requirements and expressed the urgent need to increase the quality of public spending.